Impact of glyphosate on morphophysiological traits of RR corn plants under drought stress - de Oliveira Neto, Sebastião Soares [UNESP]; Bossolani, João William [UNESP]; de Freitas, Sérgio Esteves [UNESP]; Gazola, Bruno [UNESP]; Gonçalves, Ana Stella Freire [UNESP]; Zoz, Tiago; Calonego, Juliano Carlos [UNESP] (Springer Nature, 2023)
Recent biotechnological advances have made it possible to obtain glyphosate-resistant corn genotypes and, therefore, the large-scale use of products for weed management. Usage of this systemic, non-selective herbicide can accentuate the water deficit effects in prolonged drought periods during the initial development of some crops. This work aimed to study the physiological and biochemical effects of glyphosate on RR corn plants under water deficit conditions. Cultivars were screened, and then the glyphosate effects on RR corn plants under water deficit were tested in an experiment with four cultivars (two tolerant and two susceptible), two water regimes (30 and 80% of available water), and two rates of glyphosate application (with and without). Water deficit affected all traits evaluated in glyphosate-resistant corn cultivars, reducing leaf area, and shoot and root dry biomass by more than 60%. Our results show that the application of glyphosate in RR corn plants can be carried out without negatively impacting corn plants under moderate water deficit up to 44 days after emergence. In the absence of water deficit, glyphosate increased the leaf area of RR corn plants compared to those that did not receive the product. The glyphosate application negatively impacted the length and root volume of RR corn hybrids in the two water regimes evaluated.
Keywords: Crop systems; Drought stress; Genetically modified organisms; Glyphosate effect on plants; Zea mays L